Brightness versus darkness: The influence of stimulus intensity on the distractor-response binding effect - Ruth Laub; Christian Frings (Acta Psychologica, 2021)
The intensity of a stimulus has been found to have a distinct impact upon response processes (e.g., response speed, response force, & response selection). For instance, reaction times are faster to bright than to dim stimuli (e.g., Kohfeld, 1971). In the present study, we investigated the possible influence of stimulus intensity on binding processes. According to binding theories, stimulus and response features are integrated together in short-lived memory traces, called event files (Hommel, 1998). Any re-encounter with one of these integrated features leads to the automatic retrieval of the previously constructed event file and thus of the response. Thereby bindings between stimuli (relevant and irrelevant) and responses have a direct impact on behavior. In the present experiment, we presented distractors with increasing stimulus intensity and found that intensity did exert an influence on binding processes. However, our results suggest that distractor intensity per se has no direct influence on the binding effect (the more intense a distractor is, the larger the binding effect), but that distractor intensity has an indirect effect on binding via grouping due to similarity between target and distractor intensity.